DAMPAK PUBLISITAS NEGATIF CYBER ABUSE MELALUI TINDER PADA REMAJA DI KOTA SURABAYA - Annisa Dwi Safitri; Zainal Abidin Achmad; Heidy Arviani; Saifuddin Zuhri; Ratih Pandu Mustikasari; Augustin Mustika Chairil (Metacommunication: Journal of Communication Studies, 2022)
The existence of the online dating application Tinder has changed people's behavior patterns in terms of finding a mate. Tinder does make it easier to find a mate, but some people give a negative assessment. Many Tinder users abuse the app, causing negative publicity. For example, news about the mutilation incident in the Kalibata City apartment, fraud and theft of motorbikes in the city of Banyumas, and sexual predators using the Tinder application. This negative publicity can cause a change in the attitude of teenagers using Tinder. This study aims to describe the acceptance of teenagers in Surabaya to negative news about the Tinder application. This study uses a qualitative method with a virtual ethnographic approach. Data collection techniques through participant observation, and interviews with six informants. Reception analysis using the encoding-decoding model from Stuart Hall. The results showed that negative news about the Tinder application resulted in the emergence of anxiety and worry for its users. This educates Tinder users to be more careful and selective in choosing a mate (negotiated positional). This study concludes that negative publicity raises awareness among Tinder users that crime can take place through online dating apps. The Tinder app needs to be 18 years old to download and install. Teenage users need to be more aware of the potential for cyber abuse through Tinder.